Pengaruh Kecerdasan Interpersonal dan Penguasaan Tata Bahasa terhadap Hasil Belajar Bahasa Inggris Siswa - Zenal Aripin, Asep Ahmad (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2023)
The objectives of this research are to analyze and to know about: The Effect of Grammar Mastery on The Student's Learning Outcome. The method used in this research is a survey with correlational and multiple regression techniques. In this study, the target population are the students of class X,XI, and XII at MA Subono Mantofani and MA Islamiyah. Next, the affordable population in this study are students of class X at MA Subono Mantofani and MA Islamiyah. The number of target and affordable populations in this study are 575 students. The sample in this study are X at MA Subono Mantofani and MA Islamiyah with a total of 60 students. The researcher will use a simple random sampling technique for gaining the sample of this research. The Student's English Learning Outcome will be measured using multiple choice. Interpersonal Intelligence will be measured using a questionnaire with a Likert scale and Grammar Mastery will be measured using multiple choice. The data analysis technique used SPSS 22. The result of the research are 1. There is a significant Effects of Interpersonal Intelligence And Grammar Mastery Towards The Students Learning Outcome at Private Senior Islamic High School in South Tangerang City. This is evidenced by the value of sig = 0.000 0.05 and F count = 9.811. 2. There is a significant Effects of Interpersonal Intelligence Towards The Students Learning Outcome at Private Senior Islamic High School in South Tangerang City. This is evidenced by the value of sig = 0.001 0.05 and t count = 3.399. 3. There is a significant Effects of Grammar Mastery Towards The Students Learning Outcome at Private Senior Islamic High School in South Tangerang City. This is evidenced by the value of sig = 0.033 0.05 and t count = 2.181.